Are International Students “Cash Cows”? - Choudaha, Rahul (International Higher Education, 2017)
In search for solutions to overcome financial challenges, higher education institutions have spotted the opportunity of recruiting international students as a new source of cash flow. Many institutions are on a slippery slope of milking international students as cash cows without investing in their success. Institutions must innovate to balance recruitment with reinvestment in student experiences and outcomes.